2011
DOI: 10.5402/2011/645450
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Significance of the Number of Removed and Metastatic Lymph Nodes and Lymph Node Ratio in Breast Carcinoma Patients with 1–3 Axillary Lymph Node(s) Metastasis

Abstract: We evaluated the prognostic significance of lymph node ratio (LNR), number of metastatic lymph nodes divided by number of removed nodes in 924 breast carcinoma patients with 1–3 metastatic axillary lymph node(s). The most significant LNR threshold value separating patients in low- and high-risk groups with significant survival difference was 0.20 for disease-free survival (P < 0.001), 0.30 for locoregional recurrence-free survival (P < 0.001), and 0.15 for distant metastasis-free survival (P < 0.001), and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
5
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 36 publications
1
5
0
Order By: Relevance
“…Accordingly, the proportion between affected and removed LNs was demonstrated as a stronger factor of non-sentinel LN than the previous ones (25). We observed that this proportion is a strong prognostic factor similar to the literature (28)(29)(30), especially in pN1 patients, in the opposite direction with the f a v o r a b l e o b s e r v a t i o n s t o t h e d e -e s c a l a t i o n o f axillectomy.Results from NSABP B-32 trial, the only with sufficient power in relation to the prognostic impact of SLNB (11), help to contextualize the present problem. With balanced systemic and radiation therapy between arms the two arms (SLNB versus SLNB + ALND) (31), did not observe difference on overall survival or disease-free between arms (31, 32), but showed significantly increased risk of disease progression and a trend (p = 0.08) of increased death in patients with occult disease (32).…”
Section: Discussionsupporting
confidence: 88%
“…Accordingly, the proportion between affected and removed LNs was demonstrated as a stronger factor of non-sentinel LN than the previous ones (25). We observed that this proportion is a strong prognostic factor similar to the literature (28)(29)(30), especially in pN1 patients, in the opposite direction with the f a v o r a b l e o b s e r v a t i o n s t o t h e d e -e s c a l a t i o n o f axillectomy.Results from NSABP B-32 trial, the only with sufficient power in relation to the prognostic impact of SLNB (11), help to contextualize the present problem. With balanced systemic and radiation therapy between arms the two arms (SLNB versus SLNB + ALND) (31), did not observe difference on overall survival or disease-free between arms (31, 32), but showed significantly increased risk of disease progression and a trend (p = 0.08) of increased death in patients with occult disease (32).…”
Section: Discussionsupporting
confidence: 88%
“…Based on these findings and the results of our two previous studies on series of patients having TNM N1 [32] and N3 [33] disease showing that LNR can be used to separate patients into low‐risk and high‐risk groups with significantly different survival, we investigated the most significant LNR threshold value to separate patients in two prognostic risk groups in each TNM nodal group in this large series. The patients with fewer than 10 lymph nodes removed were included in the series to reflect everyday clinical data.…”
Section: Discussionmentioning
confidence: 90%
“…Prognosis deteriorates with an increasing number of involved axillary lymph nodes. According to the TNM classification of the American Joint Committee on Cancer (AJCC)/International Union Against Cancer (UICC), lymph node involvement is categorized into three groups depending on the number of metastatic axillary lymph nodes: N1, 1–3 involved lymph nodes, N2, 4–9 involved lymph nodes and N3, more than 9 metastatic lymph nodes [9] . This might be skewed as the number of metastatic axillary lymph nodes is governed by the number of excised and examined lymph nodes.…”
Section: Discussionmentioning
confidence: 99%
“…According to recent studies, the lymph node ratio (the ratio of involved lymph nodes to the removed ones) is more useful [9] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation